Peran BUMDes Hendrosari dalam Pengembangan Ekonomi Lokal sebagai Upaya Kemandirian Ekonomi Desa - Zhafirah Desvalieta Vianny; Betty Silfia Ayu Utami (Jurnal Ekonomi dan Bisnis Digital, 2025)
Village economic development is a crucial component of national development strategy, aiming to achieve equitable prosperity and village self-sufficiency. Law Number 6 of 2014 concerning Villages grants authority to villages to manage local potential through Village-Owned Enterprises (BUMDes). This research aims to analyze the role of BUMDes Hendrosari in local economic development as an effort to realize village economic self-sufficiency. The research method used is descriptive qualitative with a literature study approach, through the review of academic literature, policy documents, and publications related to BUMDes management. The results show that BUMDes Hendrosari successfully transformed the village's image from an "intoxicating village" to an educational tourism village through the development of Lontar Sewu Edu-Tourism. This strategy not only increased tourist visits but also encouraged the growth of local MSMEs, such as restaurants with typical milkfish dishes and siwalan-based beverages. BUMDes' contribution to village economic self-sufficiency is reflected in increased job opportunities, growth of Village Original Income (PADes), and reduced community dependence on external aid. However, challenges remain, including dependence on a single tourism icon, limitations in human resource capacity, uneven community participation, and competition with other tourist destinations in Gresik. This research affirms that the success of BUMDes Hendrosari depends not only on local potential but also on participatory, innovative, and sustainable governance.